Milk exosomes are bioavailable and distinct microRNA cargos have unique tissue distribution patterns - Sonia Manca (Nature Portfolio, 2018)
Abstract Exosomes participate in cell-to-cell communication, facilitated by the transfer of RNAs, proteins and lipids from donor to recipient cells. Exosomes and their RNA cargos do not exclusively originate from endogenous synthesis but may also be obtained from dietary sources such as the inter-species transfer of exosomes and RNAs in bovine milk to humans. Here, we assessed the bioavailability and distribution of exosomes and their microRNA cargos from bovine, porcine and murine milk within and across species boundaries. Milk exosomes labeled with fluorophores or fluorescent fusion proteins accumulated in liver, spleen and brain following suckling, oral gavage and intravenous administration in mice and pigs. When synthetic, fluorophore-labeled microRNAs were transfected into bovine milk exosomes and administered to mice, distinct species of microRNAs demonstrated unique distribution profiles and accumulated in intestinal mucosa, spleen, liver, heart or brain. Administration of bovine milk exosomes failed to rescue Drosha homozygous knockout mice, presumably due to low bioavailability or lack of essential microRNAs.